2011
DOI: 10.1111/j.1651-2227.2011.02446.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Children are exposed to temptation all the time’– parents’ lifestyle‐related discussions in focus groups

Abstract: Parents struggled to give their children a healthy lifestyle and the 'temptations' of daily unhealthy choices causing hassles and conflicts. Parents desired professional support from preschool, Child Health Care and a collective responsibility from society with uniform guidelines. Parents groups were mentioned as peer support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 29 publications
3
43
0
2
Order By: Relevance
“…A child's own preferences for more sedentary behaviours were cited as largely negative influences by parents and care providers . Parents and carers also stated that children generally had a preference for use of electronic media over more active pursuits .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A child's own preferences for more sedentary behaviours were cited as largely negative influences by parents and care providers . Parents and carers also stated that children generally had a preference for use of electronic media over more active pursuits .…”
Section: Resultsmentioning
confidence: 99%
“…
Parents are responsible for young children's lifestyle; they can't make their own choices, we have to make their choices …. (P)
I feel that adults play a crucial role in the physical activity of children. If adults after dinner sit in front of the TV, kids would sit in front of the TV as well.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research indicates that parents with children living at home experience time pressure to a greater extent than others [12,13]. Previous studies have as well indicated that parents of young children perceive time pressure to be challenging to health lifestyles of their children and family [14,15] and that time pressure can have negative effects on parental mental health [16,17]. Parents’ experiences of time pressure have previously been found to be associated with lack of support, financial stress, long working hours and parenting younger children [18].…”
Section: Introductionmentioning
confidence: 99%